The Role of ICT in Breaking a Vicious Cycle of Poverty - Rashid, Siti Masayu Rosliah Binti Abdul; Hassan, Fatimah; Samat, Narimah (The journal of contemporary issues in business and government, 2021)
Poverty reduction is a global effort to achieve the Sustainable Development Goals (SDGs). The use of Information Communication and Technology (ICT) to identify the marginalized community has been determined. In Malaysia, government intervention through ICT is extended to rural women entrepreneurs to boost the economy, thus reducing poverty. Studies have identified the importance of ICT in helping rural women entrepreneurs in this poverty dilemma. A total of 186 online women entrepreneurs registered with Malaysian telecenter were selected as respondents in this study. The results show that 94 percent of respondents earn more than RM931 per month, Poverty Line Income (PLI) Malaysia, 2014. The results show that ICT users in business activities can improve households and self-success from poverty. From a social and economic perspective, the government’s intervention in introducing ICT to rural women entrepreneurs has given them many opportunities to break the previous poverty cycle.